Carbohydrate intake, glycemic load and blood glucose levels of diabetes mellitus patients in Community Health Center of Surakarta City - Farah Hayati Adibah; Siti Zulaekah (Warta LPM, 2022)
Purpose: This study aims to determine the association between carbohydrate intake and glycemic load with fasting blood glucose levels.